Two new species of orchids from the state of Morelos, Mexico - Espejo Serna, Adolfo; López-Ferrari, Ana Rosa; Jiménez Machorro, Rolando; Sánchez Saldaña, Luis; García Cruz, Javier (Instituto de Ecología, A.C., 2002)
Two new species from the state of Morelos, Mexico, are described and illustrated, Malaxis ribana Espejo & López-Ferrari and Habenaria uncata R. Jiménez, L. Sánchez & García-Cruz. Both species were collected in the surroundings of the city of Cuernavaca.